Association between new indices in the locomotive syndrome risk test and decline in mobility: third survey of the ROAD study - Yoshimura, Noriko (J Orthop Sci, 2015)
BACKGROUND: We aimed to clarify the association between new indices in a locomotive syndrome risk test and decline in mobility. METHODS: In the third survey of the Research on Osteoarthritis/osteoporosis Against Disability (ROAD) study, data on the indices were obtained from 1575 subjects (513 men, 1062 women) of the 1721 participants in mountainous and coastal areas. As outcome measures for decline in mobility, we used the five-times-sit-to-stand test (FTSST) and walking speed with cutoff values of 12 s and 0.8 m/s, respectively. RESULTS: We first estimated the prevalence of the indices in locomotive syndrome risk test stage 1, including two-step test score <1.3, difficulty with one-leg standing from a 40-cm-high seat in the stand-up test, and 25-question GLFS score ≥7, which were found to be 57.4, 40.6, and 22.6 %, respectively. Next, we investigated the prevalence of the indices in locomotive syndrome risk test stage 2, including two-step test score <1.1, difficulty with standing from a 20-cm-high seat using both legs in the stand-up test, and 25-question GLFS score ≥16, which were found to be 21.1, 7.9, and 10.6 %, respectively. Logistic regression analysis using slow FTSST time or slow walking speed as the objective factor, and presence or absence of indices as the independent factor, after adjusting for confounders, showed all three indices in both stages 1 and 2 were significantly and independently associated with immobility. Finally, we clarified the risk of immobility according to an increasing number of indices in both stages 1 and 2 and found that the odds ratio for both slow FTSST time and slow walking speed increased exponentially. CONCLUSION: We found that the three indices independently predicted immobility and that accumulation of indices increased the risk of immobility exponentially. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00776-015-0741-5) contains supplementary material, which is available to authorized users.